MORPHOLOGICAL CHANGES IN TONGUE TISSUES IN EXPERIMENTAL ANIMALS WITH SIMULATING RHEUMATOID ARTHRITIS - Povsheniuk, A.V.; Kulygina, V.M.; Kapytsia, V.M.; Shinkaruk-Dykovytska, M.M.; Tepla, T.O.; Pylypiuk, O.Yu.; Gadzhula, N.G. (World of Medicine and Biology, 2021)
In order to identify the nature of morphological changes in the mucous membrane and muscles of the tongue in the development of rheumatoid arthritis, we conducted a simulation of autoimmune disease – adjuvant arthritis in 15 rats according to A.G. Kurygin’s method. It is represented by single intradermal injection into the hind leg pads of a complete Freund’s adjuvant, followed by daily reproduction of immobilization stress from 14 to 28 days of the experiment. Adjuvant arthritis development was accompanied by deterioration of the general condition of rats and clinical signs of local and generalized inflammatory response. Histological examination revealed changes in the epithelium (dilation of intercellular spaces, vacuolar degeneration and necrosis of epithelial cells), systemic connective tissue disease (destruction, edema, stratification and loosening of collagen fibers, histio-lymphocytic infiltration) and generalized vascular pathology (edema of interstitial tissue, perivascular hemorrhages, impaired vascular wall integrity, plethora and hemorrhage). The detected changes indicated a possible negative impact of rheumatoid arthritis on the condition of tongue tissues, deepening and burdening of the pathological process in the oral mucosa with the development of comorbid conditions.